2016
DOI: 10.1513/annalsats.201508-543oc
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Biomarkers in Pulmonary Arterial Hypertension

Abstract: Rationale: Pulmonary arterial hypertension (PAH) is a rare progressive disease of the pulmonary vasculature that is characterized by endothelial dysfunction, inflammation, and right ventricular dysfunction.Objectives: The main objective was to determine whether endothelial, inflammatory, and cardiac biomarkers would be associated with the World Health Organization functional assessment and survival in patients with PAH. Methods:We performed a retrospective cohort study of patients with PAH enrolled in the Rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 48 publications
2
36
1
1
Order By: Relevance
“…Serum albumin concentration level was among the strongest predictors of mortality of the studied clinical, hemodynamic, echocardiographic, and laboratory parameters on multivariate analysis. This finding is consistent with studies in other patient populations …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Serum albumin concentration level was among the strongest predictors of mortality of the studied clinical, hemodynamic, echocardiographic, and laboratory parameters on multivariate analysis. This finding is consistent with studies in other patient populations …”
Section: Discussionsupporting
confidence: 93%
“…Although pulmonary artery pressures, functional capacity assessments, and patient symptoms are used to guide therapies, prognostication can still be challenging . Studies have identified age, blood pressure, renal function, and biomarker abnormalities as predictors of adverse prognosis, and these clinical variables can be helpful in discussing prognosis with patients and guiding therapy . Although serum albumin concentration has been found to be an important prognostic indicator in numerous other disease processes, limited data are available in the PAH population .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in adult PAH patients, 24-h excretion levels of TXB 2 are increased, as compared with normal controls, whereas, in contrast, 24-h excretion of 2,3-dinor-6-keto-prostaglandin F 1α (a stable metabolite of prostacyclin) are significantly decreased [29]. Results from a recent randomised clinical trial of Aspirin and Simvastatin (ASA-STAT) showed that PAH patients with higher levels of TXA 2 were associated with more advanced disease, and with worse clinical outcome/survival [30]. With regards to the TP, employing radioligand binding studies, its expression was shown to be significantly elevated in the right ventricles (RVs) from PAH patients compared to non-diseased controls [31].…”
Section: Discussionmentioning
confidence: 99%
“…Markers of endothelial injury continue to be a focus of research. An initial prospective study of treatment-naive patients found elevated levels of von Willebrand factor (vWF) at baseline to be associated with worse outcome, and a more recent study of patients treated for PAH found low vWF levels to be predictive of worse outcome (14,15). The investigators also observed an inverse association with lung transplant-free survival per 50-mg/dl reduction in total cholesterol, although a mechanism to account for this observation and findings related to vWF in PAH remains unresolved (16,17).…”
Section: Novel Biomarkers In Pahmentioning
confidence: 99%